Durability of cryoballoon left atrial appendage isolation: Acute and invasive remapping electrophysiological findings. Issue 6 (23rd April 2019) - Bordignon, Stefano; Chen, Shaojie; Perrotta, Laura; Bologna, Fabrizio; Nagase, Takahiko; Konstantinou, Athanasios; Weise, Felix; Fuernkranz, Alexander; Schmidt, Boris; Chun, Julian K. R.
Abstract: Background: The left atrial appendage (LAA) has been identified as a potential source of atrial fibrillation (AF) and has been described as the "fifth" pulmonary vein (PV). We report our initial experience in LAA isolation (LAAI) using the cryoballoon (CB) and data on durability of CB‐LAAI. Methods: Patients treated with a CB‐LAAI were retrospectively identified. Six weeks after electrical LAAI, patients were scheduled for staged percutaneous LAA closure. During the second procedure, a subset of patients underwent invasive remapping of the LAA. Results: A total of 32 patients (21 males, 68 ± 10 years old) were treated with CB‐LAAI. Acute LAAI was achieved in 29 of 32 (91%) patients: single‐shot LAAI was observed in 18 of 32 (56%) patients. Acute procedural sustained LAAI was related with a significantly shorter time to LAAI (sustained LAAI: 84 ± 50 s vs nonsustained LAAI: 166 ± 76 s, P  = 0.004). Mean procedure and fluoroscopy time were 61 ± 29 and 8 ± 6 min, respectively. One left‐sided phrenic nerve palsy occurred. In 25 of 32 (78%) patients, a second procedure for percutaneous LAA closure device implantation was performed. In 22 patients, persistency of LAAI was tested: durable LAAI was documented in 16/22 patients (73%). Conclusion: In the present report, CB LAA isolation followed by staged LAA closure appeared to be safe and feasible but more data are required. Time to LAAI played a role in predicting acute sustained LAAI rate. CB LAA ablation leads to 73% of durable LAA isolation.